2020
DOI: 10.20944/preprints202007.0718.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Lactate and Lactate Clearance Condition on the Prognosis of Sepsis in Children

Abstract: Objectives: To investigate the value of early lactate dynamic monitoring index in predicting prognosis of patients with sepsis and septic shock. Methods: We performed our test on 50 patients. Out of 50 patients, 28 are male, and 22 are female. Prospectively studied pediatric patients with septic shock were performed. Vital signs, Lactate clearance, were obtained at presentation 6 h, 12 h, 24 h over the first 48 h of hospitalization. The therapy received, outcome parameters of mortality and duration of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Serial measurements of lactate or lactate clearance can help predict organ failure and mortality (32), and Hasan et al (33) have suggested that the appropriate lactate cut-off value is >3.08 mmol/L at 6 h after admission. However, there is variation in the reported cut-off values for lactate in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Serial measurements of lactate or lactate clearance can help predict organ failure and mortality (32), and Hasan et al (33) have suggested that the appropriate lactate cut-off value is >3.08 mmol/L at 6 h after admission. However, there is variation in the reported cut-off values for lactate in this setting.…”
Section: Discussionmentioning
confidence: 99%